Chlorophyll fluorescence in guanandi tree (Calophyllum brasiliense) after herbicide application - ARALDI,R. (2015)
Chlorophyll fluorescence is currently used as a rapid diagnostic and nondestructive method to detect and quantify damage on the photosynthetic apparatus of leaves on weeds, crops and ornamental/coniferous trees in response to both environmental stress and herbicides. This study aimed to evaluate chlorophyll fluorescence in guanandi plants (Calophyllum brasiliense) after application of different postemergence herbicides. The experiment was performed in a completely randomized design, with six treatments (control, bentazon, sulfentrazone, isoxaflutole, atrazine and glyphosate) and five replications. The herbicide treatments were applied with a stationary sprayer, and electron transport rate (ETR) was subsequently analyzed with OS5p Multi-Mode Chlorophyll Fluorometer. In the monitored period, guanandi plants subjected to atrazine showed higher sensitivity to chlorophyll fluorescence than the other treatments. Although bentazon is a photosystem II inhibitor, it showed no major changes in electron transport for the studied species and in the monitored period. In summary, ETR is a good parameter to evaluate the effect of some herbicides on Calophyllum brasiliense plants.